Integrating online training and knowledge sharing among teachers through a cloud-based video platform - Jun Peng; Yi Dai; Yue Li (Knowledge Management & E-Learning: An International Journal)
This study integrates knowledge sharing into traditional teacher training to enhance teachers’ professional development. It addresses the research gap in implementing such integration by developing a video cloud platform that supports online training and knowledge-sharing among teachers. The proposed approach combines the SECI model (socialization, externalization, combination, and internalization) with the video cloud platform to create a new model of teacher e-learning, fostering collaborative learning among teachers in a remote and interactive context. To demonstrate the effectiveness of this approach, the study conducted experiments with Chinese primary and secondary school teachers. The new model was applied in an online professional competence-oriented supporting environment. The results showed a significant improvement in organization and management skills, and a moderate increase in technical literacy, learning, and development capabilities among the participating teachers. These findings have important implications for professional development of teachers, particularly in the context of the ongoing epidemic and the shift towards a networked and intelligent world. By integrating knowledge sharing into traditional training, teachers can enhance professional competence and adapt to the changing educational landscape. The video cloud platform is a valuable tool for facilitating collaborative learning and knowledge creation among teachers.